POSTPARTUM VULVAL LIP HAEMATOMA AND ITS MANAGEMENT IN NON-DESCRIPT DOE - RANGASAMY, S; SARATH, T; SATHIAMOORTHY, T; RAJASUNDARAM, R C (The Indian Journal of Animal Reproduction, 2023)
A case of postpartum vulval lip haematoma in a doe was presented in this paper.